Antimicrobial Susceptibility of Coagulase-Positive and Coagulase-Negative Staphylococci in Ready-to-Eat Sashimi. Issue 1 (2nd January 2017) - Moura, Ana T.; Saraiva, Cristina; Miguéis, Samuel; Esteves, Alexandra; Fontes, Maria C.
ABSTRACT: The aim of this study was to investigate the antimicrobial susceptibility pattern of Staphylococcus spp. isolated from sashimi meals collected in Japanese restaurants from northern Portugal. One hundred and thirty-six isolates of Staphylococcus spp. were recovered from sashimi samples. The antimicrobial susceptibility test showed high levels of resistance to β-lactams, macrolides, and lincosamides. All Staphylococcus isolates were sensitive to trimethoprim-sulfamethoxazole, ciprofloxacin, and chloramphenicol. Multidrug-resistant staphylococci (25%) were found in sashimi samples. It is of the utmost need to improve the hygienic practices in handling in order to reduce the occurrence of Staphylococcus species, potentially resistant to antimicrobial agents.